Repeat Transurethral Resection for Non-muscle-invasive Bladder Cancer: An Updated Systematic Review and Meta-analysis in the Contemporary Era - Yanagisawa, Takafumi; Kawada, Tatsushi; von Deimling, Markus; Bekku, Kensuke; Laukhtina, Ekaterina; Rajwa, Pawel; Chlosta, Marcin; Pradere, Benjamin; D'Andrea, David; Moschini, Marco; Karakiewicz, Pierre I; Teoh, Jeremy Yuen-Chun; et al. (European urology focus, 2024)
CONTEXT: Repeat transurethral resection (reTUR) is a guideline-recommended treatment strategy in high-risk non-muscle-invasive bladder cancer (NMIBC) patients treated with transurethral resection of bladder tumor (TURBT); however, the impact of recent procedural/technological developments on reTUR outcomes has not been assessed yet. OBJECTIVE: To assess the outcomes of reTUR for NMIBC in the contemporary era, focusing on whether temporal differences and technical advancement, specifically, photodynamic diagnosis and en bloc resection of bladder tumor (ERBT), affect the outcomes. EVIDENCE ACQUISITION: Multiple databases were queried in February 2023 for studies investigating reTUR outcomes, such as residual tumor and/or upstaging rates, its predictive factors, and oncologic outcomes, including recurrence-free (RFS), progression-free (PFS), cancer-specific (CSS), and overall (OS) survival. We synthesized comparative outcomes adjusting for the effect of possible confounders. EVIDENCE SYNTHESIS: Overall, 81 studies were eligible for the meta-analysis. In T1 patients initially treated with conventional TURBT (cTURBT) in the 2010s, the pooled rates of any residual tumors and upstaging on reTUR were 31.4% (95% confidence interval [CI]: 26.0-37.2%) and 2.8% (95% CI: 2.0-3.8%), respectively. Despite a potential publication bias, these rates were significantly lower than those in patients treated in the 1990-2000s (both p < 0.001). ERBT and visual enhancement-guided cTURBT significantly improved any residual tumor rates on reTUR compared with cTURBT based on both matched-cohort and multivariable analyses. Among studies adjusting for the effect of possible confounders, patients who underwent reTUR had better RFS (hazard ratio [HR]: 0.78, 95% CI: 0.62-0.97) and OS (HR: 0.86, 95% CI: 0.81-0.93) than those who did not, while it did not lead to superior PFS (HR: 0.74, 95% CI: 0.47-1.15) and CSS (HR: 0.94, 95% CI: 0.86-1.03). CONCLUSIONS: reTUR is currently recommended for high-risk NMIBC based on the persistent high rates of residual tumors after primary resection. Improvement of resection quality based on checklist applications and recent technical/procedural advancements hold the promise to omit reTUR. PATIENT SUMMARY: Recent endoscopic/procedural developments improve the outcomes of repeat resection for high-risk non-muscle-invasive bladder cancer. Further investigations are urgently needed to clarify the potential impact of the use of these techniques on the need for repeat transurethral resection in the contemporary era.
Keywords: Neoplasm, Residual; Non–muscle-invasive bladder cancer; výsledek terapie; uretra; Humans; Repeat transurethral resection; Urethra; lokální recidiva nádoru; lidé; cystektomie; Neoplasm Invasiveness; Transurethral resection of bladder tumor; reoperace; Cystectomy; En bloc resection; Non-Muscle Invasive Bladder Neoplasms; Treatment Outcome; Reoperation; invazivní růst nádoru; Neoplasm Recurrence, Local; reziduální nádor; nádory močového měchýře neinvadující svalovinu; Photodynamic diagnosis